Gastric adenocarcinoma associated with adenomyoma of the stomach. Issue 756 (October 1988) - Chapple, C. R.; Muller, S.; Newman, J.
Abstract : We report a case of gastric adenomyoma contiguous with adenocarcinoma of the stomach. Although a similar association is well recognized in the duodenum, we believe this to be the first documented case in the stomach. We review the literature on adenomyomata and discuss the implications of this finding. It would appear that glandular and cystic intramural lesions of the stomach are a heterogeneous group, and while there is a well established association between gastric carcinoma and gastritis cystica profunda, the same does not apply to gastric adenomyoma.